(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Throughout the last several years, banks have undergone a major overhaul in their structureand architecture. The working circumstances and regular routines of representatives have been modifiedas a result of new innovation and improved methods to structuring the operation. By constantly changingbusiness and working circumstances, the deregulation of markets, the rise of new technology, and thedevelopment of new types of employment have dramatically reshaped working life. Organizationalaffiliation and the well-being of the working population are directly impacted by this kind of circumstance.In light of the recent rise in psychosocial concerns among workers, the financial sector is particularlydeserving of a thorough analysis.It relies on primary data taken from a sample of 182 residents ofMuvattupuzha and Thodupuzha municipalities. A pre-drafted and pre-tested Questionnaire is used togather the data. The findings of this research shed light on the main sources of occupational stress andthe variables that influence it among bank personnel. Overwork, technology, a lack of training, jobautonomy, customer relationships, grievance redress, and the work-home interface are the mostimmediate sources of stress. Individuals are affected by these elements to varied degrees and indifferent ways.